Sound and vibration energy harvesting for railway applications: A review on linear and nonlinear techniques. (November 2021) - Hosseinkhani, A.; Younesian, D.; Eghbali, P.; Moayedizadeh, A.; Fassih, A.
Abstract: Energy harvesting in the railway industry has great potential for many applications. Energy harvesters can provide electrical power for track-side, on-board, and infrastructure instruments, including health monitoring sensors, signaling, switches, and safety equipment. Due to the rapidly growing trend of the railway network, a considerable number of instrumentations need to be located in inaccessible, remote, and harsh locations where providing the energy through cable is almost impossible. In these cases, self-powered sensors and distributed power generators can be used based on energy harvesting techniques. High-intensity sound and vibration levels in the railway environment prove them to be promising sources of energy for self-powered devices. This paper aims to provide a comprehensive review on the railway sound and vibration energy harvesting, from the beginning to the most state-of-the-art. This paper addresses different energy harvesting resources for the railway environment, diverse methods of energy harvesting and their advantages and drawbacks, and at the end, energy harvesting applications in the railway industry. Different models and prototypes of energy harvesters are introduced and compared. Finally, the potential applications of railway energy harvesting are addressed, and future challenges and trends are discussed. The scheme of the present paper is designed in a way to provide readers the most significant principles that need to be considered in the design of railway energy harvesters. Highlights: One of the first systematic reviews in sound/vibration energy harvesting in railway. Overview of key advantages and drawbacks of different applied techniques. Detailed review of applications in track-side and rail car on-board instruments. New techniques including tribo-electricity, auxetic materials and nonlinear concepts. Directions on the challenges and future research lines in railway energy harvesting.